Characterization of Bi based superconducting whiskers - Chung, M; Verebelyi, DT; Schneider, CW; Nevitt, MV; Skove, MJ; Payne, JE; Marone, M; Kostic, P (ELSEVIER SCIENCE BV, 1996)
We have made a thorough characterization study of Bi-based cuprate superconducting whiskers. Undoped, Gd-doped and Pb-doped Bi2Sr2Can-1CunOx (n = 2, 3) whiskers were grown using a technique developed by Matsubara et al. Chemical compositions were determined by X-ray dispersive electron microprobe and wet chemistry. The resistance and magnetic flux shielding effect were measured as a function of temperature. We used AC calorimetry to make the first measurements of the heat capacity of a single whisker of this material. The whiskers were found to contain a mixture of the 2212 and 2223 phases, although flux shielding and X-ray diffraction showed only the 2212 phase.
Keywords: CA-CU OXIDE; SINGLE-CRYSTAL; GROWTH; PHASE; THERMODYNAMICS; BI2SR2CACU2OX; TRANSITIONS; SAMPLES; SYSTEM; HEAT